Industrial Bearing Fault Detection Using Time-Frequency Analysis - Bella, Y.; Oulmane, A.; Mostefai, M. (Engineering, Technology & Applied Science Research, 2018)
Time-frequency fault detection techniques were applied in this study, for monitoring real life industrial bearing. For this aim, an experimental test bench was developed to emulate the bearing rotating motion and to measure the induced vibration signals. Dedicated software was used to analyze the acquired measurements in the time-frequency domain using several distributions with varying resolution. Results showed that each fault type exhibits a specific behavior in the time-frequency domain, which is exploited in the localization of the faulty component.